Risk, Uncertainty and Government - O'Malley, Pat (The GlassHouse Press, 2004)
Both risk and uncertainty are neo-liberal concepts, which can be viewed as complementary techniques for governing diverse aspects of life, rather than natural states of things. This new book examines the way these constructs govern the production of wealth through 'uncertain' speculation and 'calculable' investment formulae.